Daily calcium profile in diagnosis of hypo- and hypercalcemia in patients with chronic hypoparathyroidism. clinical case series - E. V. Kovaleva; A. K. Eremkina; N. G. Mokrysheva (Ожирение и метаболизм, 2021)
Hypoparathyroidism is a rare endocrine disorder characterized by hypocalcemia and hyperphosphatemia, due to absent or inappropriately low serum parathyroid hormone (PTH) levels. The chronic postoperative hypoparathyroidism accounts approximately 75% of patients; the genetic, autoimmune or idiopathic forms are significantly less common. Today, chronic hypoparathyroidism remains the last major endocrine deficiency, for which hormonal replacement therapy has not found widespread use. Achieving the target levels of phosphorus-calcium metabolism is an important factor of the disease control, required for the prevention of short- and long-term complications. The standard therapy with active metabolites/analogues of vitamin D (alfacalcidol, calcitriol) and calcium supplements does not always allow to achieve the target treatment goals. Despite high doses of calcium and active vitamin D, some patients suffer from unstable calcium levels and associated symptoms.The measurement of serum calcium and phosphorus in the early morning hours remains the main laboratory tests for such patients, but in sometimes this diagnostic approach does not really reflect the true picture.The presented clinical cases describe the changes of both hyper- and hypocalcemia within one day in patients with chronic postsurgical hypoparathyroidism managed by standard therapy.